Millennial wine consumers: Risk perception and information search - Thomas Atkin; Liz Thach (Wine Economics and Policy, 2012)
Marketing managers in the US have long been concerned with how to reach young consumers most effectively and how to present important information. This research demonstrates how the information search and risk reduction strategies of Millennials differ from older consumers. Findings from a survey sample of 409 US consumers suggest that if unsure about making a wine selection, Millennials are more apt to seek information from friend/family and shelf talkers than elders. Elders were more willing to ask questions of store personnel and wine stewards. While brand is very important to both groups, Millennials rely less on geographical cues such as region of origin to determine wine quality and pay more attention to medals won, label imagery, and alcohol content. The differences in the importance of and usage of these various information sources are helpful for wineries to prioritize their marketing appeals to the Millennial segment.
Keywords: 330; Consumer behavior; Information search; Millennials; Risk perception; Wine label